Conditions of Convergence Almost Everywhere for the Convolution of a Function with Delta-Shaped Kernel to this Function - Bushev, D. M. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish sufficient conditions for the convergence of the convolution of a function with delta-shaped kernel to this function. These conditions are used for the construction of the subspaces of solutions of differential equations and systems of these equations isometric to the spaces of real functions.